2016
DOI: 10.1038/srep36436
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 ameliorates liver fibrosis through miR-200a/beta-catenin

Abstract: IL-22 ameliorates liver fibrosis by inhibiting hepatic stellate cells (HSC), and loss of miR-200a is associated with the development of liver fibrosis. The study aimed to investigate the interplay between IL-22 and miR-200a in regulating liver fibrosis in vivo and in vitro. We observed that IL-22 significantly reduced the proliferation of HSC and increased the expression of p-STAT3. β-catenin was identified as a target gene of miR-200a by luciferase reporter assay, and upregulation of miR-200a significantly at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
3
27
0
1
Order By: Relevance
“…In accordance with their finding, a previous study of our collaborators demonstrated a positive correlation of miR‐200a with IL‐6, of which increased levels were linked to higher morbidity and mortality rates in HIV patients receiving cART . While the role of miR‐200a in liver fibrosis is controversial in recently published studies, we could not find an association of miR‐200a with liver fibrosis.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with their finding, a previous study of our collaborators demonstrated a positive correlation of miR‐200a with IL‐6, of which increased levels were linked to higher morbidity and mortality rates in HIV patients receiving cART . While the role of miR‐200a in liver fibrosis is controversial in recently published studies, we could not find an association of miR‐200a with liver fibrosis.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with the previous finding that miR-200a is a key player in a variety of disease models associated with fibrosis, including pancreatic fibrosis [ 26 ], liver cirrhosis [ 27 ], and obstructive nephropathy [ 14 ], Xu et al found that miR-200a was down-regulated in TGF-β1-activated pancreatic stellate cells and miR-200a mimic reversed the increased expression of mesenchymal markers vimentin and ECM proteins by activating the PTEN/Akt/mTOR pathway [ 26 ]. In the process of liver fibrosis, Yang et al found that overexpression of miR-200a reduced the SIRT1 expression, consequently preventing activation and proliferation of hepatic stellate cells [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Simonian and Liang et al reported that IL-22 protected against Bacillus subtilis- and bleomycin-induced lung fibrosis in mice, respectively [ 9 , 20 ]. In liver fibrosis, although Wu et al found that IL-22 activated hepatic stellate cells and mediated fibrogenesis in patients with hepatitis C [ 21 ]; most studies reported a protective role of IL-22 in liver fibrosis [ 22 , 23 ]. In the cardiovascular system, Rattik et al found that knockout of IL-22 reduced the collagen area of aortic roots in atherosclerosis in mice [ 13 ].…”
Section: Discussionmentioning
confidence: 99%